The therapy top measurement and visualization system - An example for the advancements in existing sports equipments - Kranz, M.; Holleis, P.; Spiessl, W.; Schmidt, A.; Tusker, F. (International Journal of Computer Science in Sport, 2006)
In this paper we report on ongoing work where sensor technology and wireless networks are integrated with sports equipment to improve the utility and usability of such equipment. Our focus is on the iterative design process for a multidisciplinary team. We show how mutual learning became a central issue for the success of the design and development.